An Observational Study of Cerebral Blood Flow Velocity Evaluation in the Prone Position During Posterior Lumbar Surgery. (August 2019) - Bombardieri, Anna Maria; Beckman, James; Urban, Michael; Go, George; De Gaudio, A. Raffaele; Girardi, Federico P.; Ma, Yan; Memtsoudis, Stavros G.
Abstract : BACKGROUND: Prone positioning (PP) is necessary for surgical access during posterior spine procedure. However, physiological changes occur in the PP. Typical findings are a decrease in arterial blood pressure and in cardiac output that could potentially lead to an alteration in cerebral perfusion. Therefore, we decided to study cerebral blood flow velocity (CBFV) with transcranial Doppler ultrasonography to evaluate the effect of the PP on cerebral hemodynamics. METHODS: Twenty-two patients undergoing spine surgery in the PP were studied. General anesthesia was induced using 250 μg of fentanyl, 2 mg/kg of propofol, and 0.1 mg/kg of vecuronium, and was maintained with 0.25%–0.5% isoflurane, 50% nitrous oxide in oxygen, continuous infusion of 100 μg/kg/min of propofol, 1.5 μg/kg/h of fentanyl, and 0.15 mg/kg/h of ketamine. Continuous invasive arterial blood pressure, heart rate, electrocardiogram, and end-tidal carbon dioxide were monitored. CBFV with transcranial Doppler in the middle cerebral artery was first measured with the patients under general anesthesia in the supine position. Patients were then placed in the PP and remained in this position throughout surgery. CBFV, end-tidal carbon dioxide, heart rate, and blood pressure were measured continuously for 75 minutes after initiation of PP. This coincided with surgical exposure and minimal blood loss. Data were analyzed every 15 minutes for statistical significant change over time. RESULTS: Mean arterial blood pressure decreased 15 minutes after the installation of the PP and onward, but this decrease was not statistically significant. CBFV syst (the maximal CBFV during the systolic phase of a cardiac cycle) and CBFV mean (the time averaged value of the maximal velocity envelope over 1 cardiac cycle) did not vary at any time points. CBFV diast (the CBFV just before the acceleration phase [systole] of the next waveform) was lower at T3 (30 minutes after PP) compared to T1 (value derived averaging the first measure in the PP with the ones at 5 and 10 minutes) ( P = .01), and the pulsatility index was higher at T5 (60 minutes after PP) compared to T0 (baseline, patient supine under general anesthesia) ( P = .04). Data were analyzed at specific time points (T0 and T1). This value was derived by computing an average of the CBFV values collected at the first measure in the PP and at 5 and 10 minutes thereafter: T2, 15 minutes after PP; T3, 30 minutes after PP; T4, 45 minutes after PP; T5, 60 minutes after PP; and T6, 75 minutes after PP. CONCLUSIONS: Our data on CBFV during PP for spine surgery demonstrate preservation of cerebral perfusion during stable systemic hemodynamic conditions. The present results do not allow us to determine whether the PP would be similarly tolerated with increasing length of surgery, variations in systemic hemodynamics, and in different patient populations.